Seneca - Baker, Karen, 1965- (New York : Greenwillow Books, 1997)
After choosing a horse for her own, a young girl takes care of it, goes for rides, and visits it each day.
Elem. School Library Collection.
School Library Journal.
Bulletin (Center for Children's books).
3.5
K-3
Keywords: Horses -- Fiction; Horses -- Fiction; Horses -- Fiction